Determination of the half-life of gadolinium-148. (April 2023) - Chiera, Nadine M.; Dressler, Rugard; Sprung, Peter; Talip, Zeynep; Schumann, Dorothea
Abstract: The half-life of the alpha-emitter 148 Gd was measured using the "direct method", in which the number of atoms is directly determined and their activity is then measured. Pure Gd samples containing megabecquerels of 148 Gd were obtained by reprocessing proton-irradiated tantalum material. Multicollector-inductively coupled plasma mass spectrometry was performed to determine the amount of 148 Gd atoms retrieved. The activity of the 148 Gd atoms contained in the Gd sample was measured by means of alpha-spectrometry. The half-life of 148 Gd was deduced to be 86.9 years, with a combined uncertainty of 4.5%. Highlights: Gd-148 samples were obtained by reprocessing proton-irradiated tantalum. The number of Gd-148 atoms in the sample was determined by MC-ICP-MS. Alpha-spectroscopy was used to determine the activity of Gd-148 in the sample. The half-life obtained for Gd-148 is (86.9 ± 3.9) years.